Media encounters: Models of TV program adaptation to digital platforms (Raparin Journal of Humanities (RJH), 2025)
This paper aims to articulate the media evolution on how the old media species compete with new ones to adapt to the new conditions of the media ecology, in an ecosystem, when new media species emerge, old species try to adopt to the new paradigm. In this case, how Television deals with the new media environment? What are the main methods that television has to deal with to adopt to the new condition of media environments? in what ways, television has to alter programming and distribution strategies and practices to follow the new media species characteristics. The Television adaptation in the age intermediality present on two distinctive approaches; first intermediality operates as a fundamental condition or category between mediums, while the second approaches as a category of specific individual media products. As one the scientific attempts in the field of theorizing the media ecology, this paper, thematically deals on Television adaptation to other media platforms, as a case study it analyzes the tv program of Kurdsat channel during the past two decades. The paper concludes that with emergence a new communication and media platform such as VOD, and social media platforms etc., Kurdish Televisions tries to adopt with news screens (digital TV, Tablet and mobile phone) by developing new windows of transmedia and somehow imitating the characteristics new media species.